2021
DOI: 10.1109/access.2021.3121700
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for an Active PV Array to Improve System Efficiency During Partial Shading

Abstract: Owing to time-varying external environmental influences, undesirable string mismatches frequently occur in photovoltaic (PV) power generation systems, which will cause conventional PV systems to experience extremely severe power losses. Under partial shading conditions (PSCs) caused by passing clouds, neighboring buildings, and animal excrement, the characteristic curve of the PV string becomes complicated with multiple peaks, which increases the difficulty of determining the maximum power point (MPP) of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Even in solar PV systems, a large amount of solar radiation energy is wasted in the form of heat energy, which leads to low energy conversion efficiency [10,11]. Recent research studies have reported the various methods of improving the efficiency of the PV system [12][13][14][15]. Extracting the maximum power from the PV cells by the maximum power point tracking (MPPT) control technique is one of the simple and easiest ways to obtain better efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Even in solar PV systems, a large amount of solar radiation energy is wasted in the form of heat energy, which leads to low energy conversion efficiency [10,11]. Recent research studies have reported the various methods of improving the efficiency of the PV system [12][13][14][15]. Extracting the maximum power from the PV cells by the maximum power point tracking (MPPT) control technique is one of the simple and easiest ways to obtain better efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency, execution, difficulty, irretrievable energy, and total cost are just a few of the important variables that need to be taken into consideration while constructing the MPPT method for PV systems. On the above basis these, various MPPT approaches turned out and categorized into three main groups [7,8]. The first type of MPPT technique calculates MPP using a priori data rather than continuously monitoring the current and voltage [9,10].…”
mentioning
confidence: 99%